Detecting muscle strain in professional football players through plasma myoglobin levels - Saita, Y.; Yamamoto, N.; Fukushima, Y.; Izawa, H.; Idadate, D.; Harada, K.; Ohyama, T.; Inoue, J.; Ishijima, M. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Muscle issues such as soreness, cramps, and strains are common consequences of sports exercise, making it critical to accurately identify the nature of muscle discomfort. It is important for not only medical professionals but also athletes and sports enthusiasts to independently identify and manage the risk of muscle strain.